Digital learning initiatives forging inclusive education in post-conflict nations - Siddiqullah Barikzai; Vijayakumar Bharathi S; Arif Perdana (Cogent Education)
The transition to a post-conflict nation presents numerous challenges for higher education. This study explores the advantages and impediments of implementing digital learning in Afghan higher education institutions (HEIs). Digital learning in Afghan HEIs currently falls short of stakeholder expectations and requirements. Authorities and key stakeholders, however, have taken measures to address these issues and ensure seamless integration of digital learning into HEIs. Efforts have been made to promote digital learning and improve access to higher education for disadvantaged groups, which could expand educational opportunities and foster diversity, equity, and inclusion, particularly among girls in Afghanistan. Our research employed an interpretive field approach, conducting interviews with 102 participants across 12 Afghan universities—eight public and four privates—to examine the challenges and opportunities associated with digital learning initiatives and inclusive education in a post-conflict setting. We also recommended ways to improve digital learning and promote inclusive education in the country. Our findings provide recommendations for digital and policy strategies to enhance the digital learning experience and promote inclusive education in post-conflict nations. The experiences and lessons learned from Afghan HEIs offer valuable insights for developing more accessible, engaging, and effective online education models.